Cracking during thermal post-processing of laser powder bed fabricated CM247LC Ni-superalloy. (15th July 2019) - Boswell, John H.; Clark, Daniel; Li, Wei; Attallah, Moataz M.
Abstract: The causes of cracking during thermal post-processing of laser powder bed fabricated (LPBF) CM247LC Ni-superalloy have been examined. Micro-hardness measurements and microstructural analyses were undertaken following short aging heat treatments around the phase transformation temperatures identified by Differential Scanning Calorimetry (DSC) analysis of the as-built condition. Results showed a steep increase in cracking density in the samples between 450 °C and 600 °C, which corresponded to changes in the microstructure, hardness, and elastic modulus. A combination of ductility dip cracking and strain age cracking mechanisms were identified as the primary causes of cracking in LPBF CM247LC following post-build thermal treatments. The results of this work shed light on the relationship between the heat treatment temperatures and the onset of post-build cracking, and could help develop post-LPBF heat treatments for high γ′ Ni-superalloys. Graphical abstract: Unlabelled Image Highlights: Cracking due to post-processing of laser fabricated Ni-superalloys was studied. Mechanisms were associated with different heat treatment temperatures. The mechanisms are ductility dip cracking and strain age cracking. Microstructural evidence was obtained to elucidate the cracking mechanisms.